ISSUES OF JUSTICE IN THE VIEWS OF ABU ABDULLAH RUDAKI - Adiz Abdullaevich Azimov (International Journal of Literature and Language Studies, 2026)
This article analyzes the views of Abu Abdullah Ja'far bin Adam Rudaki Samarkandi, a great Eastern thinker and poet known as the "Father of Humanity," on the concept of justice. Rudaki paid particular attention to the primacy of justice and the preeminence of human interests in society. He also examined the justice and humanism of a ruler. Rudaki paid particular attention to the primacy of justice and the supremacy of human interests in society. He also examined the justice and humanism of a ruler. The poet Rudaki emphasizes that a ruler must be so just that even his enemies see him as a manifestation of justice. Thinkers from Europe and the East have studied Abu Abdullah Rudaki's views on justice and acknowledged that his works remain relevant today. According to Rudaki, a person who lacks compassion for the poor and is incapable of doing good is a person who has lost their humanity. Rudaki's philosophical and ideological views embody profound humanistic ideas and a commitment to social justice. According to Rudaki, a person who lacks compassion for the poor and is incapable of doing good is a person who has lost their humanity. Rudaki's philosophical and ideological views are deeply humanistic and strive for social justice. Rudaki emphasizes compassion and kindness, a concern for the suffering of the poor and oppressed, and their unwavering support. He believes that human society should be based on mutual assistance and kindness. Rudaki's views remain relevant today and are of great importance in the context of nurturing a well-rounded individual.